Professional health regulation in the public interest : international perspectives - Chamberlain, John Martyn, 1972-; Dent, Mike, 1944-; Saks, Mike (Bristol, UK : Policy Press, 2018)
Bringing together leading academics worldwide, this collection compares and critically examines the ways in which different countries are regulating healthcare in general, and health professions in particular, in the interest of users and the wider public.
1. Introduction: professional health regulation in the public interest -- 2. Health care governance, user involvement and medical regulation in Europe -- 3. The informalisation of professional-patient interactions and the consequences for regulation in the United Kingdom -- 4. The regulation of health care in Scandavia: professional, the public interest and trust -- 5. Medical regulation for the public interest in the United Kingdom -- 6. Regulating the regulators: the rise of the United Kingdom Professional Standards Authority -- 7. Regulation and Russian medicine: whither medical professionalisation? -- 8. Patterns of medical oversight and regulation in Canada -- 9. Let the consumer beware: maintenance of licensure and certification in the United States -- 10. Governing complementary and alternative medicine(CAM) in Brazil and Portugal: implications for CAM professionals and the public -- 11. Birth of the hydra-headed monster: a unique antipodean model of health workforce governance -- 12. Health complaints entities in Australia and New Zealand: serving the public interest? -- 13. Trust and regulation of health systems: insights from India.
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: Medical care -- Standards; Medical personnel; Medical policy; Medical care -- Quality control; Health Policy; Delivery of Health Care -- standards; Health Personnel -- standards; Quality Assurance, Health Care; Professionalism; Personnel médical.; Politique sanitaire; Soins médicaux -- Qualité -- Contrôle.; Soins médicaux -- Normes; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Medical policy; Medical care -- Quality control; Medical care -- Standards; Medical personnel; Electronic book